Merging Satellite and in situ Data to Assess the Flux of Terrestrial Dissolved Organic Carbon From the Mackenzie River to the Coastal Beaufort Sea - Bertin, Clément; Matsuoka, Atsushi; Mangin, Antoine; Babin, Marcel; Le Fouest, Vincent (Frontiers in Earth Science, 2022)
In response to global warming, the Arctic is undergoing rapid and unprecedented changes that alter the land-to-sea forcing in large Arctic rivers. Improving our knowledge of terrestrial dissolved organic carbon (tDOC) flux to the coastal Arctic Ocean (AO) is thus critical and timely as these changes strongly alter the biogeochemical cycles on AO shelves. In this study, we merged riverine in situ tDOC concentrations with satellite ocean-color estimates retrieved at the land-marine interface of the Mackenzie Delta to make a first assessment of the tDOC export from its main outlets to the shelf. We combined tDOC and river discharge data to develop a regression model that simulated tDOC concentrations and fluxes from daily to interannual (2003-2017) time scales. We then compared the simulated satellite-derived estimates to those simulated by the model constrained by in situ tDOC data only. As the satellite tDOC estimates reflect the delta effect in terms of tDOC enrichment and removal, our results inform us of how much tDOC can potentially leave the delta to reach the ocean (1.44 ±0.14 TgC.yr-1). The chemodynamic relationships and the model suggest contrasting patterns between Shallow Bay and the two easternmost delta outlets, which can be explained by the variability in their geomorphological settings. At the seasonal scale and for all outlets, the satellite-derived tDOC export departs from the estimate based on in situ tDOC data only. During the river freshet in May, the satellite-derived tDOC export is, on average, ~15% (Shallow Bay) to ~20% (Beluga Bay) lower than the in situ-derived estimate. This difference was the highest (-60%) in 2005 and exceeds 30% over most of the last decade, and can be explained by qualitative and quantitative differences between the tDOCin situ and tDOCsat datasets in a period when the freshet is highly variable. In contrast, in summer and fall, the satellite-derived tDOC export is higher than the in situ-derived estimate. The temporal difference between the satellite and in situ-derived export estimates suggests that predicting seasonal tDOC concentrations and fluxes from remote Arctic deltas to the coastal AO remains a challenge for assessing their impact on already changing carbon fluxes.